THE ROLE OF HUMAN RESOURCE MANAGEMENT IN IMPROVING STREET VENDOR BUSINESS IN KUTA MANDALIKA - Wardhana, Galih Wisnu; Santoso, Rukun; Hadi, Bawa Mulyono; Mamuki, Emiliyan; Tasrif, Mohammad Jon (Jurnal Ilmiah Global Education, 2023)
This study aims to examine the role of human resource management in improving street vendor business in Kute Mandalika and the obstacles passed in increasing street vendor business in Kute Mandalika. This research was conducted using a qualitative approach. Data analysis techniques are the process of systematically searching and compiling data obtained from interviews, field notes, and other materials so that they can be easily understood and the findings can be informed to others. The result of this study is that the role of human resources in street vendors in Kute Mandalika is very important in increasing the income of the people there. With this, traders can manage their trades. Street vendors can compete fairly with other vendors. The obstacle that is often experienced is the lack of knowledge of street vendors about their trade management. Awareness of street vendors’ compliance with local government regulations.